UJI KEMANFAATAN KLINIS LIDOKAIN 2%+ ADRENALIN 1:80.000 ANTARA GENERIK DIBANDINGKAN BRENDED - Abdul Rochim (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Lidocain is widely used in dentistry especially in treatment as local anaesthetic is commonly used as a 2 % solution containing 1:80.000 adrenalin. Lidocain has two types of generic name and brand names (e.g. elokain, extracaine, ikacain, Xylestesin, pehacaine, and lidonest, etc). Government’s rules (Permenkes No 085/Menkes/Per/I/1989 and Permenkes No HK.02.02/Menkes/068/I/2010) must use Generic drugs in public health services, but professional dentists commonly use lidocain branded. Aim of study is to compare the efficacy of Lidocain adrenalin generic vs.Lidocain adrenalin branded in clinical use. Material and Methods: A total of 60 students of dentistry Faculty Jember Unversity was divided into two groups, consisting of 30 patients Generic lidocain and 30 branded lidocain. They were locally injected as block anaesthesia. The onset of the drugs was determined by sensation paraesthesia of the lower lip. The duration of the drugs was determined from onset until sensation of paraesthesia disappeared. Result: Mean of onset Generic lidocain adrenalin was 174 seconds, and that of branded lidocain adrenalin was 220 seconds. Mean of duration Generic lidocain adrenalin was 137,61 minutes, while that of branded lidocain adrenalin was 130 minutes. Conclusion : There was no difference in the efficacy between Generic lidocain adrenalin and branded lidocain adrenalin (p > 0,05).